FAKTOR FAKTOR YANG MEMPENGARUHI LOYALITAS PELANGGAN TERHADAP PRODUK PERALATAN RUMAH TANGGA TUPPERWARE (Di PT. Nazila Jambi Nugraha) - Dinda, Dinda; Afrila, Diliza (Universitas Batanghari Jambi, 2022)
The aims of this study were (1) to determine the level of customer loyalty to Tupperware home appliance products at PT Nazila Jambi Nugraha, and (2) to determine the factors that influence customer loyalty to Tupperware home appliance products at PT Nazila Jambi Nugraha. The method used in this study is the Ex Post Facto research method, namely empirical investigation, and the researcher does not control the independent variables directly, because basically there is no manipulation of the embodiment of these variables. According to Sugiyono (2012: 17) Ex Post Facto research is a study conducted to examine events that have occurred and then trace back to find out the factors that can cause these events to arise. The population of this study were 402 customers of Tupperware household products at PT Nazila Jambi Nugraha. The sample of this research is 24 people. The results showed that (1) Customer loyalty to Tupperware household appliance products could be identified using a questionnaire with the indicator Consistency in buying behavior on the sub-indicator of not switching brands even though there were cheaper ones in the highest respondent value with a TCR of 97.5%, namely very satisfactory, (2) Internal factors that influence loyalty are assessed by respondents with a TCR of 87.5%, namely satisfactory. Meanwhile, the psychological indicators related to beliefs and attitudes were rated with a TCR of 85.83%, namely satisfactory, and (3) External factors that influenced loyalty were assessed by respondents at 78.83%, namely satisfactory. Whereas on the Social Factors indicator related to the family sub-indicator, the respondent's value with a TCR of 87.5% is satisfactory.Keywords: Customer Loyalty, Tupperware